Answer:
The simplified form of the given expression is 12(m -n).
Step-by-step explanation:
The given expression is

We need to simplify the given expression.
Rearrange the terms according to the variables.

On combining like terms, we get

On simplification, we get


Taking GCF common.

Therefore the simplified form of the given expression is 12(m -n).
Answer:
-0.394875
Step-by-step explanation:
(9/16)*(-3/4)
9/16=.5265
-3/4=-.75
.5265*(-.75)=-0.394875
Answer:
3?
Step-by-step explanation:
im not sure tho
Answer:
<h2>12</h2>
Step-by-step explanation:
To evaluate 4P2, we will use the permutation formula as shown;
nPr = 
4P2 = 

4P2 = 12